BASYTAMA CONCEPTS OF SHARIA FINANCIAL LITERATURE ACCELERATION IN PREPARING EXCELLENT HUMAN RESOURCES BASED ON VILLAGE COMMUNITIES - Daffa Redika Fauzi; Fatimah Adzakiyah Shalihah; Prisilia Hadi; Dian Purnomo Jati (Airlangga International Journal of Islamic Economics and Finance, 2021)
Indonesia's Islamic finance sector (Halal Finance) is experiencing rapid growth. In a pandemic situation, Islamic banking grows consistently. It recorded that in 2020, Islamic banking grew by 9.22%. Based on the Islamic Finance Development Index issued by the Islamic Corporation for the Development of the Private Sector (ICD), Indonesia's Islamic finance industry managed to climb to rank two after previously occupying the 4th position. The productive age of the population also has considerable potential to increase the number of Islamic bank customers in Indonesia. This is also becoming more potential because based on data from the Central Statistics Agency in 2019 Indonesia has 83,820 villages. However, on the other hand, based on a survey from the Financial Services Authority (OJK) in 2019, the Islamic financial literacy index of the Indonesian people only reached 8.93%. Based on the potential and existing problems, this study aims to develop a concept of public interest in using Islamic bank products through the Bank Syariah Kita Bersama (Basytama) program which is part of a community empowerment strategy and builds superior human resources through the development of community-based Islamic financial ecosystem institutional aspects. village. This research is based on descriptive qualitative analysis. This is supported by the use of primary and secondary data, in primary data collection we use distributing questionnaires to people and conducting interviews by telephone or virtual conference based on in-depth interviews. contact. In addition, to help support research to obtain more comprehensive and extensive data, we also use secondary data through library research, using various trusted and credible reference sources. The conceptual model of Basytama focuses on aspects of Islamic banking, empowerment, and education in rural communities. We base this concept on Basytama programs such as collecting and distributing funds, collaborating with stakeholders at the village level, opening assistance programs, and researching village potentials through the Basytama Institute so that it is hoped that an increase in the competence and standard of living of the community will be achieved accompanied by an increase in the quality of life. Islamic financial literacy at the village level.